Analysis of the important factors inhibiting surplus management in auditing - Wu, Yueying (2022)
This paper focuses on the analysis of the influence of audit factors on the suppression of surplus management, based on the fact that previous literature has mostly discussed the relationship and interaction between audit and surplus management, or mainly only on whether audit can control surplus management, while this paper is a pioneer in not only verifying the suppressive effect of audit on surplus management, but also analyzing the degree of influence of five important factors on surplus management behavior, which are Audit fee, auditor competence, audit tenure, audit opinion, and firm size. The CSMAR database in China was used to find the data of listed companies for the five years from 2017 to 2021 as the research sample, and then the data was sorted and aggregated by excel, and then the data was processed and analyzed by stata, and finally it was concluded that these five audit factors do have a suppressive effect on surplus management, and the degree of their influence in descending order is audit opinion>audit fee>audit fee>audit fee>audit fee. firm size > auditor competence > audit tenure.